Illegal activities, but still value added ones (?): size, causes, and measurement of the shadow economies all over the world - Friedrich Schneider (Johannes Kepler University of Linz, Department of Economics, 2000)
Using various methods estimates about the size of the shadow economy in 76 developing, transition and OECD countries are presented. The average size of the shadow economy (in percent of GDP) over 1989-93 in developing countries is 39 %, in transition countries 23 % and in OECD countries 12 %. An increasing burden of taxation and social security contributions combined with rising state regulatory activities are the driving forces for the growth and size of the shadow economy. According to some findings, a growing shadow economy has a negative impact on official GDP growth, however, this result is not robust, other studies show the opposite effect.
Keywords: O17; O5; D78; H2; H26; 330; Schattenwirtschaft; Wirtschaftswachstum; Welt